Inputs of organic carbon from Ria de Aveiro coastal lagoon to the Atlantic Ocean - Lopes, C. B.
Land/ocean boundaries constitute complex systems with active physical and biogeochemical processes that affect the global carbon cycle. An example of such a system is the mesotidal lagoon named Ria de Aveiro (Portugal, 40 38/N, 08 45W), which is connected to the Atlantic Ocean by a single channel, 350 m wide. The objective of this study was to estimate the seasonal and inter-tidal variability of organic carbon fluxes between the coastal lagoon and the Ocean, and to assess the contribution of the organic carbon fractions (i.e. dissolved organic carbon (DOC) and particulate organic carbon (POC)) to the export of organic carbon to the Ria de Aveiro plume zone. The organic carbon fractions fluxes were estimated as the product of the appropriate fractional organic carbon concentrations and the water fluxes calculated by a two-dimensional vertically integrated hydrodynamic model (2DH). Results showed that the higher exchanges of DOC and POC fractions at the system cross-section occurred during spring tides but only resulted in a net export of organic carbon in winter, totalling 85 t per tidal cycle. Derived from the winter and summer campaigns, the annual carbon mass balance estimated corresponded to a net export of organic carbon (7957 ¼ 6585 tyr-1 POC þ 1372 tyr-1 DOC). On the basis of the spring tidal drainage area, it corresponds to an annual flux of 79 gm-2 of POC and 17 gm-2of DOC out of the estuary.